2016
DOI: 10.1186/s40862-016-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of EFL learners’ demotivation, perceptions of classroom activities, and mastery goal in predicting their language achievement and burnout

Abstract: The present study aims at delving into English as foreign language students' demotivation, burnout, mastery goal orientation, and perceptions of classroom activities. This is accomplished by building a causal structural model through which the associations among the constructs are estimated. The Persian version of the 'de-motivation scale' designed by Sakai and Kichuki (System 37:57-69, 2009) is used to assess demotivation. It measures six constructs: teachers, characteristics of classes, experiences of failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 68 publications
1
36
1
1
Order By: Relevance
“…Thus, the second issue that warranted further qualitative inquiry is the inconsistency of the present findings with those from previous studies (Jahedizadeh et al, 2016;Macayan, 2012a;Macayan & San Jose, 2013). In contrast with the previous studies, in learning English as L2, it seems the performance orientation is the most adaptive form of goal orientation.…”
Section: Adaptive Performance Goal Orientation In a L2contrasting
confidence: 52%
See 1 more Smart Citation
“…Thus, the second issue that warranted further qualitative inquiry is the inconsistency of the present findings with those from previous studies (Jahedizadeh et al, 2016;Macayan, 2012a;Macayan & San Jose, 2013). In contrast with the previous studies, in learning English as L2, it seems the performance orientation is the most adaptive form of goal orientation.…”
Section: Adaptive Performance Goal Orientation In a L2contrasting
confidence: 52%
“…L2 motivation researchers endorse increasing students' goal-orientedness (Dörnyei & Csizer, 1998), understanding language learning 'goal orientations' or 'the reasons why a task is undertaken ' (p. 466), and raising the explicitness of goal orientation (Griffiths & Oxford, 2014). For one, Jahedizadeh et al (2016) used Midgley et al's (1998 Achievement Goal Orientation Inventory and found that mastery goals, along with other student factors, had positive effects on students' achievement.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…For about quarter century, researchers have been working on motivating factors in language learning process and how individuals are motivated as well as focusing on factors that decrease their motivation, or the demotivating factors. (Butt, Khosa, Malghani, Khosa, & Bukhari, 2016;Jahedizadeh et al, 2016, Al-Sharief, 2013Challa, 2015;Rashidi, Rahimi, & Alimorad, 2014;Sundqvist & Scheller, 2013). It is a relatively new area of investigation, and it has been suggested to involve different mechanisms from those involved in motivation (Kim & Kim, 2015), and it is accepted as the darker side of the motivation by Hirvonen (2010).…”
Section: Demotivation In Language Learningmentioning
confidence: 99%
“…They have attempted to determine the reasons why some students have problems in FL classes (Mohammadi, 2014). In the domain of education and specifically in the field of foreign language learning (EFL), students may face various obstacles such as learning conditions, teachers' methodologies and behaviors, inappropriate materials, or lack of learning facilities or equipment (Jahedizadeh et al, 2016).…”
Section: Demotivation In Language Learningmentioning
confidence: 99%
See 1 more Smart Citation